(untitled) (Homoeopathy for All, 2025)
Thyroid dysfunction has become increasingly common in Indian urban populations, including Bhopal, Madhya Pradesh. Disorders such as hypothyroidism and hyperthyroidism can severely affect metabolism, mental health, pregnancy outcomes, and cardiovascular function. This study examines the prevalence, risk factors, and health implications of thyroid dysfunction among the general population in Bhopal. Based on existing epidemiological data, hospital records, and public health surveys, the research identifies young women, pregnant individuals, and those with metabolic disorders as high-risk groups. The study highlights the urgent need for public health interventions, including routine screening, improved iodine nutrition, and targeted awareness programs in the region.